2009
DOI: 10.1111/j.1442-200x.2009.02920.x
|View full text |Cite
|
Sign up to set email alerts
|

US health‐care crisis

Abstract: Access to primary care doctors has been shown in studies across the world to result in better patient outcomes, increased satisfaction with care and lower health-care costs. Primary care is the entry point for most patients into the health-care system and focuses on prevention, chronic care management and availability for sick care. Primary care offices providing continuous, coordinated and accessible care are called medical homes. Changing disease patterns and increased amounts of chronic care has increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Although this legislation highlighted the unique role of primary-care physicians to lower health care costs in an integrated complex health-care system, any push to increase the number of primary care physicians (PCPs) in the United States may come at the cost of other specialties like future surgeons. [17][18][19][20] It is important that policy makers and medical schools do not use the impending shortage of PCPs to poach potential practitioners from other specialties with lower career satisfaction.…”
mentioning
confidence: 99%
“…Although this legislation highlighted the unique role of primary-care physicians to lower health care costs in an integrated complex health-care system, any push to increase the number of primary care physicians (PCPs) in the United States may come at the cost of other specialties like future surgeons. [17][18][19][20] It is important that policy makers and medical schools do not use the impending shortage of PCPs to poach potential practitioners from other specialties with lower career satisfaction.…”
mentioning
confidence: 99%
“…Within such a system, much of the routine, timeconsuming tasks are performed by nurse practitioners and physician assistants, leaving the PCPs more time to listen to and adequately treat patients. 19,20 Previous studies regarding career satisfaction of PCPs have indicated some interesting trends and raised some important questions. Buchbinder, Melick, and Powe 22 conducted a cohort study of 507 PCPs, aged younger than 45 years, who were interviewed twice (in 1987 and again in 1991) and asked overlapping questions regarding their overall career satisfaction.…”
mentioning
confidence: 99%
“…21 The role of PCPs is bound to take on a much higher level of importance if the push toward patientcentered medical homes gains steam. 19,20 These medical homes are designed to deliver better coordinated, easily accessible, continuous, comprehensive, familycentered, and culturally sensitive primary health care with a focus on prevention, safety, quality, and appropriate reimbursement via a team approach. Within such a system, much of the routine, timeconsuming tasks are performed by nurse practitioners and physician assistants, leaving the PCPs more time to listen to and adequately treat patients.…”
mentioning
confidence: 99%
“…• High cost with marginal population outcomes (Rushton, 2009), • Insufficient primary care workforce (Berwick et al, 2008),…”
Section: The Us Health Systemmentioning
confidence: 99%